2015
DOI: 10.1515/jpem-2014-0231
|View full text |Cite
|
Sign up to set email alerts
|

Growth failure associated with early neglect: pilot comparison of neglected US children and international adoptees

Abstract: The long-lasting impact of different neglectful environments on growth in children is not well studied. Three groups of children, 3–10 years old, were recruited (n = 60): previously institutionalized international adoptees living in stable home environments for at least 2 years (IA; n = 15), children with a history of neglect born in the USA (USN; n = 17), and controls (n = 28). Children underwent physical examination, anthropometry, and collection of serum for growth parameters. Mean height standard deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…It has been recognized that "historically, institutional care has been associated with regimented, depersonalized environments in which children have no opportunity to experience a caring family life" (Powell et al 2004). As previously noted, institutions have had poor outcomes and were unresponsive to children's needs (Berens and Nelson 2015;Miller et al 2015;Morantz and Heymann 2010;Smyke et al 2007;van den Dries et al 2009;van Ijzendoorn et al 2008;Wanat et al 2010). This evidence pointed to the urgent need for deinstitutionalization and the implementation of a policy-driven process aimed at the transformation of child protection services to focus on family-level and community-level support by many governments, including Kenya (UNICEF and Republic of Kenya 2014).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been recognized that "historically, institutional care has been associated with regimented, depersonalized environments in which children have no opportunity to experience a caring family life" (Powell et al 2004). As previously noted, institutions have had poor outcomes and were unresponsive to children's needs (Berens and Nelson 2015;Miller et al 2015;Morantz and Heymann 2010;Smyke et al 2007;van den Dries et al 2009;van Ijzendoorn et al 2008;Wanat et al 2010). This evidence pointed to the urgent need for deinstitutionalization and the implementation of a policy-driven process aimed at the transformation of child protection services to focus on family-level and community-level support by many governments, including Kenya (UNICEF and Republic of Kenya 2014).…”
Section: Introductionmentioning
confidence: 91%
“…It is widely recognized that institutionalization has adverse impacts on developmental outcomes and children's well-being (Berens and Nelson 2015;Miller et al 2015;Smyke et al 2007;van den Dries et al 2009;van Ijzendoorn et al 2008). According to Berens and Nelson (2015), there is strong evidence of devastating developmental consequences for children institutionalized in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the set of data to a control cohort, the authors revealed that growth is most severely impaired in the group of children with institutional history. Also, children with a history of institutional care showed the lowest IGF-1 and IGFBP-3 levels (Miller et al 2015). The authors suggested that the different time and severity of psychosocial stress in neglected and institutionalized children resulted in different regulations of growth.…”
Section: Emotional Deprivationmentioning
confidence: 97%
“…This previously suggested effect of psychosocial stress factors on growth outcomes also was the central aspect of investigation in a study conducted by Miller et al (2015). The authors analyzed data from 60 children, which have shown a history of institutional care or emotional neglect in their familiar environment.…”
Section: Emotional Deprivationmentioning
confidence: 99%
“…Orphanages are one of the care providing institutions and it is especially children from orphanages who are diagnosed with a variety of personality disorders with varying degrees of complexity (Matějček, 2005b;B. S. Miller et al, 2015;Nelson et al, 2007;Roeber et al, 2012).…”
Section: Introductionmentioning
confidence: 99%